Reaction to World News Events and the Influence of Mass Media in an Indian Village - Poffenberger, Thomas (Michigan Papers On South And Southeast Asia, 2020)
Our major research interest in the village under study was originally in the area of socialization practices, social change and variables related to fertility behavior. We had not planned a study of the diffusion of news events and villagers' reactions to them. However, the Indian Government was considering the use of media for a major mass communication program, to propagate the idea of having small families through the use of family planning methods, and we believed it would be of value to examine any data that might be helpful in getting at least some feeling about what villagers read in the papers and what they heard on the radio, as well as their understanding of the information and their attitudes toward it. We subsequently asked questions about the use of mass media. [1]